Comparison of chronic idiopathic urticaria patients with positive and negative autologous serum skin test - Attada, Suhasini; Rao, G. Venkateswara; Kilaru, Krishna Rajesh; Nukala, Kalyani (International Journal of Research in Dermatology, 2022)
Background: Chronic urticaria, with or without angioedema, has been defined as daily or almost daily symptoms and signs recurring for more than six weeks. Chronic urticaria has an idiopathic etiology in majority. This is called as chronic idiopathic urticaria (CIU) or chronic spontaneous urticaria (CSU). Aim and objectives were to compare the clinical features in CIU patients with a positive autologous serum skin test (ASST) and negative ASST. Methods: Fifty clinically diagnosed patients of CIU attending the department of DVL OPD at tertiary care teaching hospital, were enrolled based on the inclusion and exclusion criteria. Results: ASST was positive in 48% (24/50) of patients with CSU. In study of 50 patients, 66% were females and 34% were males. The mean age of patients was 36.8 years. The disease’s median duration was 10 months and 11 months in ASST positive and ASST negative groups respectively. Of the 50 patients, 20 patients showed a positive response to the test for simple dermographism, of which 13 were ASST positive. Of the 50 patients, 8 patients gave a history of atopy, of which 5 were in the ASST positive group, 3 were in ASST negative group. Conclusions: In the present study ASST was positive in 48% of patients with CIU. Majority of ASST positive patients had almost daily attacks. ASST positive patients had a longer duration of persistence of wheals. ASST is a fairly good indicator of autoimmune etiology for chronic urticaria.